Relationship between the synthesis parameters and the morphology of manganite nanoparticle-assembled nanostructures - Leyva de Guglielmino, Ana Gabriela; Troiani, Horacio Esteban; Curiale, Carlos Javier; Sanchez, Rodolfo Daniel; Levy, Pablo Eduardo (Elsevier Science, 2007)
Fil: Leyva de Guglielmino, Ana Gabriela. Universidad Nacional de San Martín; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes; Argentina